KAJIAN SOSIAL EKONOMI PETANI KELAPA DI DESA MANGARAN KECAMATAN KABARUAN KABUPATEN KEPULAUAN TALAUD - Ino Romeo Garing; Hermon Maurits Karwur; Fonny Rewah (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2020)
This study aims to describe the Socio-Economic Study of Coconut Farmers in Mangaran Village, Kabupdate Subdistrict, Talaud Islands Regency. The research method used is a qualitative method with a descriptive approach. Data collection was carried out through observation, interview and documentation techniques. The results showed, namely: 1) the socio-economic existence of coconut farmers in the village of Mangaran has many benefits and uses for meeting their daily needs as well as main income besides cloves and nutmeg; 2) the existence of land accessibility is still inadequate so that coconut farming communities experience difficulties, especially in transporting coconut processing products to be marketed; 3) accessibility by sea still does not support, especially the existence of ships for the outbound transportation of the Talaud Islands district; 4) the selling price of coconut (copra) has decreased in 2018, below the standard of five hundred per kilo, so that the farming community is in trouble and is even embarrassed because they have to fail the panel; and 5) the role of the local government of the Talaud Islands district is still not empowering and striving for accessibility, both land and sea, and is not even able to minimize the existence of the selling price of coconut which has decreased below the standard of five hundred per kilogram. Therefore it is suggested that there should be efforts, especially by the local government of the Talaud Islands district, so that the existence of accessibility can support both land and sea, and even be able to maximize the selling price of coconut as the main income of coconut farming communities.